Response Surface Methodology (RSM) implementation in zro particles reinforced aluminium chips by Hot Equal Channel Pressing (ECAP) - Al-Alimi, Sami; Lajis, M. A.; Shamsudin, S.; Chan, B. L.; Rady, Mohammed. H.; Al-Zeqri, Musleh; Wahib, Ahmed; Aladani, Abdalkarim; Ali, Abdulaziz; Yusuf, Nur Kamilah (Springer Link, 2021)
In recent years, the interest on solid-state recycling of aluminum chips increases over the years due to the less energy consumption of the process. This research studies the quantitative effects of preheating temperature and volume fraction of Zirconium Dioxide when it is reinforced to the Aluminum alloy AA6061 on its mechanical properties. The parameters of the experiment are preheating temperature and volume fraction of ZrO . Temperature are varied between 450 and 550 ℃ according to the boundary parameters. The volume fraction of ZrO consists of 5, 10 and 15% of the reinforcement. Increasing the volume fraction of ZrO correlates with the increase of mechanical and physical properties. Design of Experimental with factorial design was implemented to analyse the magnitude of response on the mechanical properties from the variable of parameters. The preheating temperature was revealed to be the most significant factor affecting the yield strength and the microhardness of the composite followed by the volume fraction of ZrO . It is revealed that the most optimum temperature is 550 ℃ and the optimum percentage of volume fraction is 9.28%. Both highest microhardness and yield strength were obtained from these optimum temperatures. Scanning Electron Microscope (SEM) revealed on how elongation in Zirconia chips is affected by the amount of ZrO reinforcement. Energy Dispersive Spectroscopy (EDS) analysis performed revealed on the arbitrary weight out of total weight for every element in the composite such as Al, Zr, O and Si.